VERB CONJUGATION AND TENSE FORMATION IN GERMAN AND ENGLISH: A STRUCTUAL COMPARISON (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The verb conjugation and tense construction of German and English, two languages with different grammatical systems. It highlights important structural patterns in both languages by analyzing verb inflection according to grammatical person, tense and mood. The study examines how moods like subjunctive and passive are conveyed and compares regular and irregular conjugation and investigates the function of auxiliary verbs in creating future and perfect tenses. Syntactic features like verb location in German main and subordinate sentences are given particular attention. A better grasp of how each language encodes time and modality through its verbal system is made possible by the findings which shows both convergences and divergences in verbal morphology and syntax.